Cutaneous myiasis—a stowaway from Central America. (August 2017) - de Menezes, S.; Smibert, O.
Graphical abstract: A high index of suspicion should be reserved for travellers returned from endemic areas with lesions compatible with cutaneous myiasis, as early recognition may avoid progression to invasive surgical management.